Interprofessional approach to personalized medication management and therapy optimization in IBD care - Daniel Fleischmann; Benedicta Binder; Muriel Huss; Tanja Elger; Claudia Wolf; Johanna Loibl; Hauke Christian Tews; Arne Kandulski; Stephan Schmid; Martina Müller; Alexander Kratzer (Frontiers in Medicine)
A considerable number of patients with chronic inflammatory bowel diseases (IBD) are required to manage extensive polypharmaceutical regimes, which significantly elevates the risk of drug–drug interactions. Also, the disease’s impact often leads to the consumption of additional self-medication by the patients such as naturopathic remedies to alleviate disease-induced suffering and nutritional supplements to compensate for malabsorption syndromes inherent to the condition. There is a well-established consensus that polymedication coupled with unregulated supplementary intake can jeopardize the safety of drug therapy. Despite this, pharmaceutical co-supervision—proven to mitigate adverse drug events and enhance patient adherence to treatment—is generally lacking in routine clinical settings. Furthermore, the assessment of individual therapy adherence, a crucial predictive factor for therapeutic outcomes, is frequently suboptimal. In response to these issues, this study implemented an interdisciplinary approach wherein a team comprising medical and pharmaceutical professionals conducted a comprehensive survey coupled with a medication review for patients attending an IBD outpatient clinic. Employing an IBD-specific questionnaire alongside the patients’ documented medication regimens enabled the identification and subsequent discussion of current therapeutic concerns and potential medication-related risks during follow-up consultations. This intervention aimed to bolster individual patient satisfaction and enhance medication safety, ultimately fostering sustained success in IBD management.